Propagação vegetativa de umbu-cajazeira - Mendes, Nouglas Veloso Barbosa (2017)
Increased demand and appreciation by consumers for in natura or processed tropical fruit products has increased the demand of the agroindustries for fruits of native species. The ‘umbu-caja’ tree (Spondias sp.) is a tropical fruit native from Northeast Brazil and whose fruits are highly valued by pulp, juice and ice cream agroindustries. Plant propagation sexually or asexually is very difficult, therefore, until the moment are not found crops of this species, although it has high productivity. There is necessary to study the propagation methods of this species in order to raise it to the level of cultivated plant, because its exploitation is based on the extractivism. The use of products that promote rooting and, consequently, the formation of seedlings, able to accelerate the process of obtaining seedlings suitable for planting. However, there are difficulties in acquiring, preparing, dosing and applying certain products to facilitate use by nursery owners and seedlings producers. Thus, two experiments were carried out at the Experimental Field of Pacajus Embrapa – Agroindústria Tropical, to evaluate the vegetative propagation of ‘umbu-caja’ tree. We used different types of cuttings, different kinds of chemicals, different types of injuries and stakes coverage in seeking to obtain the highest percentage of rooting and seedlings suitable for planting. The use of the Sela Gel® agrochemical, the incision at the base of the stake and the coverage assist in the vegetative propagation of ‘umbu-caja’.